Molecular detection and prevalence of Theileria ovis and Anaplasma marginale in sheep blood samples collected from Layyah district in Punjab, Pakistan - Abid, Kainat; Bukhari, Sundas; Asif, Muhammad; Sattar, Ayesha; Arshad, Maryam; Aktas, Munir; Iqbal, Furhan (Springer, 2021)
Theileria ovis and Anaplasma marginale are intracellular pathogens affecting a wide range of animals, causing huge economic losses worldwide. The present study reports the molecular evidence of Theileria ovis and Anaplasma marginale in sheep blood samples (N = 218) collected from Layyah district in Punjab (Pakistan), where economy heavily relies on livestock. A 520 base pair fragment specific for 18S ribosomal RNA gene of Theileria ovis was PCR amplified in 23/218 (10.6%) sheep blood samples, while for Anaplasma marginale, a 265 base pair fragment specific for msp1b gene was generated in 15/218 (6.9%) sheep blood samples. Two blood samples were found co-infected (0.9%) with both parasites. Amplified PCR products of both parasites were confirmed by DNA sequencing and submitted to GenBank. Prevalence of both Theileria ovis (p = 0.3) and Anaplasma marginale (p = 0.4) varied non-significantly among the investigated sheep breeds. Tick burden on dogs present with sheep herds was found associated with Theileria ovis infection in sheep (p = 0.05). It was observed that lambs (p = 0.009), sheep in small herds (p = 0.04), and tick burden on dogs present with sheep herds (p = 0.01) were associated with Anaplasma marginale infection in sheep during the present study. In conclusion, we are reporting a higher prevalence of Theileria ovis than Anaplasma marginale in blood samples of sheep collected from Layyah district. Tick-infested dogs were found to be risk factors for the transmission of both pathogens in sheep, and tick control strategies should be extended to dogs associated with sheep herds in this area.
Keywords: Theileria ovis; Anaplasma marginale; PCR; Sheep; Layyah district; Phylogenetic analysis